Analisa Kapasitas Daya Dukung Fondasi Tiang Pancang untuk Mesin Boiler Pembangkit Listrik Tenaga Uap 2 x 3 MW, Kepulauan Talaud, Sulawesi Utara - DELIMA, DELIMA; Sestining Ayu, Dian ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Boiler machine’s foundation must be able to support the loads until safety factor limit. Therefore, bearing load capacity must be greater than foundation’s maximum loads. Single pile’s bearing capacity was analized by static methode from the result of laboratory soil investigation. While pile group bearing capacity was analized using pile efficiency factor. Settlement analysis of single pile has been calculated using Poulo and Davis’s method. And settlement analysis of pile groups using Skempton Method. The result from single pile’s load capacity was 1107,55 kN and pile group load capacity was 5094,684 kN. The result of pile settlement analysis that could be occured is 8,44 mm in single pile and 77,05 mm in pile group.